The biochemical effect correlated with pulmonary dysfunction and complications in obese patients - Çeltikçi, Başak; Sayın Gülensoy, Esen (Acta Medica, 2024)
Objective: Obesity, an epidemic metabolic disorder, is associated with various biochemical, inflammatory, oxidative and immunological pathways. We aimed to investigate the biochemical effect correlated with pulmonary dysfunction and complications in overweight and obese patients. Material and Methods: We aimed to evaluate retrospectively the effect of biochemical parameters on pulmonary dysfunction and complications in 79 overweight and obese patients. The correlative effect of biochemical values, including CRP, and spirometric measurements, such as forced vital capacity (FVC) and forced expiratory volume in 1 s (FEV1), on pulmonary dysfunction and complications in 79 overweight and obese patients seen in the outpatient clinic were evaluated. Body mass index (BMI), FEV1 and FVC, and total biochemistry values, including creatinine, AST, ALT and CRP values were correlated among each other. Results: Low FVC levels, leukocytosis, high AST and ALT levels, and comorbidities of obesity are significantly associated with high BMI values by univariate analysis in these patients. Higher AST levels are significantly correlated with higher leucocyte counts, and both AST and ALT levels are significantly correlated with platelet counts. Conclusion: We investigated the effect of biochemical parameters on pulmonary dysfunction and complications in obese patients. Obesity can be helpful to categorize high-risk patients with low FVC levels in the context of respiratory diseases and high AST and ALT levels for other comorbidities as steatohepatitis, diabetes mellitus and coronary artery disease. This study sheds light on future research on obese patients for prognosis of these diseases, because of their biochemical profile correlation with pulmonary dysfunction and complications.